Evaluation of integrated foundational medical curriculum from Wuhan University: a cross-sectional study based on questionnaires - Xianlong Zhou; Bingyang Lv; Xingxing He; Dongxu Li; Xiaoyang Zhang; Wei Fan; Ping Wang; Jie Liu; Mingxia Yu (Cogent Education)
The integrated curriculum was recently introduced to the foundation medical education in Chinese medical schools. In this context, Wuhan University has offered two integrated courses, ie., Cell, Molecule and Genes (CMG) and Tissue and Function (TF). The purpose of this paper is to unfold problems in the design and implementation of integrated curricula by analyzing these two courses and explore possible ways to improve them. A Likert questionnaire survey was conducted on 102 second year medical students at Wuhan University to understand their experiences in various aspects of two integrated curriculum. The result of the survey showed that students believed that integrated courses helped them better understand the contents and answer the questions in the case analysis. Students’ satisfaction with the CMG was significantly lower than that of the TF (p < 0.05) in a number of questions. Especially, 83.3% of respondents complained about the complexity of the CMG course. Both integrated courses contained many topics, but neither was well-organized. The segmented teaching format easily led to disconnections among the key points. To fully realize the potential benefits of an integrated curriculum, the teaching team responsible for each integrated course can improve content delivery by developing a systematic framework of course contents to ensure connectivity among modules and a uniform teaching format by different instructors.